Reconfigurable Photonic Generation of Binary Modulated Microwave Signals - Jialin Ma; Aijun Wen; Zhaoyang Tu; Xiangjuan Cheng; Yong Wang (IEEE Photonics Journal, 2020)
A novel photonic scheme of binary modulated microwave signals generation based on a dual-polarization quadrature phase-shift keying (DP-QPSK) modulator is proposed and experimentally demonstrated. The scheme is highly reconfigurable, amplitude keying signal (ASK), phase-shift keying signal (PSK) or frequency-shift keying (FSK) signal can be generated by appropriately setting the amplitude of the binary coding signal. The coding signal and local oscillator (LO) signals are independent with each other, binary modulated microwave signals can be generated with arbitrary coding rate and carrier frequency. The frequency deviation of the FSK signal can also be adjusted flexibly. No filter is used in the scheme and the tuning range is large. A proof-of-concept experiment is carried out to verify the feasibility of the proposed system. A 1-Gbps 8-GHz microwave ASK signal, a 0.5-Gbps 6-GHz microwave PSK signal, and a 0.5-Gbps 8/12-GHz microwave FSK signal are g[enerated in the experiment.